Investigations on the nutritional and medicinal potentials of an under exploited food plant Alocacia indica - Aberoumand, *Ali (Food Biology, 2011)
The present study investigated the nutritional and bioactive components of Alocacia indica stem of the popularly consumed vegetable in some part of Iran. The proximate analysis and bioactive constituents were determined by standard methods of AOAC, while vitamin E, micro/macro elements and fatty acids were determined using AAS and HPLC respectively. The results showed that the stem contained 5.7± 1.60% protein, 72.66± 2.10% carbohydrate, 3.29± 0.60% fat, 7.3± 0.46% ash, 11.05± 0.05% crude fiber, and vitamin E not detected. The bioactive compound found were 0.87± 3.09 mg/g phenolics, saponnins and steroids were detected. All these results indicate that the stem of this Alocacia indica contained nutrients and mineral elements that may be useful in nutrition, while the bioactive compounds explained the medicinal action of the plant stem encountered in its therapeutic uses.